A new species of Stasimopus from the eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history - Hendrixson, Brent E.; Bond, Jason E. (Zootaxa, 2004)
A new species of ctenizid trapdoor spider is described, Stasimopus mandelai sp. nov., from the Eastern Cape Province of South Africa. This species occurs syntopically with S. schoenlandi Pocock and a number of other mygalomorph spiders at the Great Fish River Nature Reserve. Illustrations, photographs, and additional notes on burrow architecture and general natural history are provided.